Commitment to conformity in the international sales contract - Hulaiel, Muneer Ali (Journal of Economic, Administrative and Legal Sciences, 2024)
The international sales contract is considered one of the important contracts in the international trade field, and the commitment to conformity is an essential part of this contract, and conformity is related to ensuring that the products or services that are sold meet the specifications and standards agreed upon between the seller and the buyer.The obligation to conform requires the seller to provide the product or service that meets the description specified in the contract, including quality, quantity, packaging, label, and timely delivery. Conversely, it requires the buyer to accept and pay for the product or service according to the terms specified in the contract.If conformity is not adhered to, the affected party has rights and means to obtain compensation, such as demanding that the product be repaired, replaced, or refunded for the money it paid. Commitment to conformity is considered essential to ensure the success of the international sales process and build trust between the seller and buyer, which contributes to reducing risks. And commercial disputes and enhancing cooperation between parties, therefore, the commitment to conformity in the international sales contract is an essential element that must be observed and applied to ensure the success of the deal and maintain a strong and profitable business relationship for both parties involved.
Keywords: international contract; international sales; compliance commitment; seller; buyer